2020
DOI: 10.22541/au.159646032.20485092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Percutaneous versus Surgical Revascularization for Acute Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is a common medical condition that requires appropriate revascularization in a timely manner. Percutaneous revascularization (PR) was the first line treatment option when feasible. Limited data is available comparing PR to surgical revascularization (SR) in the AMI setting. Study population was extracted from the 2016 Nationwide Readmissions Data using International Classification of Diseases, tenth edition codes for AMI, PR, SR, and procedural complications. Endpoints include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The lncRNAs are extensively involved in the regulation of various pathophysiological processes; H19 is an important member of this family and is closely related to ICM. Some studies (34,35) have found that H19 was present in the left ventricular tissue biopsy of patients with heart failure, and the content of H19 was more abundant in the vascular wall. It has also been detected in the heart tissue of a mouse cardiac hypertrophy model; its expression is up-regulated in the pathological state, and can inhibit cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNAs are extensively involved in the regulation of various pathophysiological processes; H19 is an important member of this family and is closely related to ICM. Some studies (34,35) have found that H19 was present in the left ventricular tissue biopsy of patients with heart failure, and the content of H19 was more abundant in the vascular wall. It has also been detected in the heart tissue of a mouse cardiac hypertrophy model; its expression is up-regulated in the pathological state, and can inhibit cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%